Life kerning : creative ways to fine tune your perspective on career & life - Ahrens, Justin, 1972- (Hoboken, N.J. : Wiley, 2012)
'Creative approaches for designing a more balanced life and careerIn the graphic design industry, kerning is the fine-tuning or adjustment of space between letterforms (type). In this book, author Justin Ahrens applies this concept to both the life and career of business professionals. There is a common misconception that positive change in one's life only comes from a complete system overhaul. Ahrens challenges this notion by inviting business leaders and professionals to not only reassess the various spaces and goals of one's life, but to rethink our understanding of balance altogether.This book includes insights and observations from both the creative and professional world. Guides you in determining what you're passionate about, and how to keep those passions in the forefront of your life and career How to create work that stands apart How to cultivate and maintain a group of wise mentors Develop critical decision-making skills Live a life that fuels your work, and work in a way that fuels your life. Life Kerning shows you how'--
Includes index.
Keywords: Creative ability in business; Self-actualization (Psychology); Creative ability; Change (Psychology)